2008
DOI: 10.1080/15332640802055640
|View full text |Cite
|
Sign up to set email alerts
|

City's Racial Composition Shapes Treatment Center Characteristics and Services

Abstract: We assessed the extent to which a city's racial composition shapes the characteristics of substance abuse treatment centers. We utilized both the 2004 National Survey of Substance Abuse Treatment Services, which provides information on treatment center characteristics such as availability of comprehensive substance abuse evaluation, and 2000 Census data on the percentage of African Americans and Latinos in a city. We found that a city's racial composition influences treatment center characteristics and service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…Of course, members of minority groups will often have less financial resources than those of the majority. Our paper, along with others show that while Blacks may experience longer times to remission, it is due to their relative lack of socio-economic and other resources compared to whites (Jacobson, Robinson, & Bluthenthal, 2007; Vélez et al, (in press)). …”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Of course, members of minority groups will often have less financial resources than those of the majority. Our paper, along with others show that while Blacks may experience longer times to remission, it is due to their relative lack of socio-economic and other resources compared to whites (Jacobson, Robinson, & Bluthenthal, 2007; Vélez et al, (in press)). …”
Section: Discussionsupporting
confidence: 54%
“…Whites typically drink more alcoholic beverages then minorities, thus, they might remit less than minorities (Arndt, Schultz, Turvey, & Petersen, 2002). However, a second study reports the opposite finding that African Americans and Latinos compared to whites are more likely to live in poor urban contexts with greater drug and alcohol availability and fewer treatment options, making it difficult to remit (Castellani, Wedgeworth, Wootton, & Rugle, 1997; Vélez, Campos, & Arndt, (in press); Walton et al, 2003). Finally, the median age of Latinos in the U.S. (25.8 years) is over 12 years younger than the median age of Whites (38.6 years).(U.S.…”
Section: Introductionmentioning
confidence: 99%
“…Do agency or state characteristics have an impact on the reported availability of services? Previous research documents a relationship between state characteristics and existing programs and policies (Baron & Straus, 1989;Barrilleaux & Bernick, 2003;Burr, Mutchler, & Warren, 2005;Douglas & Cunningham, 2008;Linksy & Straus, 1986;Vélez, Campos-Holland, & Arndt, 2008;Zimmerman, 1988Zimmerman, , 1991. Our first article from this study found a relationship between agency and state characteristics and the availability of services for IPV victims (Hines & Douglas, 2011).…”
Section: Current Articlementioning
confidence: 57%
“…The year 2003 was the year that was closest to when our data was collected. Previous research has demonstrated that state characteristics, including political ideology, predict the provision of services for members of individual states (Baron & Straus, 1989;Barrilleaux & Bernick, 2003;Burr et al, 2005;Douglas & Cunningham, 2008;Linksy & Straus, 1986;Vélez et al, 2008;Zimmerman, 1988Zimmerman, , 1991. State characteristics are an approximate measure of the context in which DV agencies operate.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation